INTEGRATING BLOOM’S TAXONOMY INTO THE ASSESSMENT OF PRODUCTIVE SKILLS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article examines the integration of Bloom’s Taxonomy into the assessment of productive language skills—speaking and writing—in contemporary language education. Bloom’s hierarchical model provides a structured cognitive framework that supports the evaluation of learners’ linguistic competence beyond surface-level accuracy. By aligning assessment tasks with the six cognitive levels—Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating—educators can design more comprehensive and pedagogically meaningful assessment tools. The study highlights how Bloom’s Taxonomy helps measure not only linguistic correctness, but also higher-order thinking and communicative performance. The paper concludes with practical recommendations for implementing taxonomy-based assessment criteria in communicative classrooms.